Kekosongan Hukum dan Ketidakjelasan Tanggung Jawab Platform E-Commerce Atas Produk Ilegal dalam Transaksi Digital - Bok Rok Su; Gunardi Lie; Moody Rizqy Syailendra Putra (CV Rewang Rencang, 2025)
Legal uncertainty and the lack of clear liability rules for e-commerce platforms regarding illegal products sold by third parties have harmed consumers. An analysis of national regulations and liability theories (fault, risk, and strict liability) reveals that platform obligations remain vaguely defined. This gap is often exploited to avoid accountability. Legal reform is necessary to prevent platforms from hiding behind intermediary status and ensure their responsibility for products circulating on their systems.